Utilization Of Butterfly Pea Instant Powder as an Antihypertension Health Drink in Dungaliyo Village, Gorontalo District - Prisca Safriani Wicita; Arlan K. Imran; Fitriah Ayu Magfirah Yunus (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Hypertension is a state of systolic blood pressure ≥140 mmHg and diastolic ≥90 mmHg. This non-communicable disease has become a problem in the world because of its increasing prevalence and its association with cardiovascular disease, stroke and kidney disease. Gorontalo Regency is a district with the highest number of hypertension sufferers and based on research data, one of the survey data for hypertension sufferers is in the Dungaliyo Village area. This community service aims to apply research results related to the use of natural ingredients in the form of butterfly pea flower (Clitoria ternatea L.) which has many benefits, one of which is antihypertensive activity. The application was realized in the form of distribution of butterfly pea flower instant powder and training for cadres/community groups related to the procedure for making butterfly pea flower instant powder. This is to increase the level of health and skills of the people of Gorontalo in general as well as the awareness of cadres/community groups where the community service is carried out in particular. This community service activity has been carried out in accordance with the objectives and methods planned in 3 (three) stages. Stage 1; Coordination with the Head of Dungaliyo village, Stage 2; Pretest understanding of hypertension and butterfly pea flowers, measurement of blood pressure and dissemination of the use of butterfly pea powder as an antihypertensive health drink, Stage 3; Socialization of butterfly pea flower cultivation, distribution of seeds, measurement of blood pressure and Posttest. This community service activity obtained the results of an evaluation of community understanding which increased from 50% to 90% and a decrease in blood pressure with the percentage of people with high blood pressure from 25% to 20 %.